Mannitol Metabolism in Lentinus edodes, the Shiitake Mushroom - Kulkarni, Rajiv K. (1990)
Mannitol metabolism was evaluated in fruiting bodies of Lentinus edodes. Cell extracts were prepared from fruiting bodies, and key enzymes involved in mannitol metabolism were assayed, including hexokinase, mannitol dehydrogenase, mannitol-1-phosphate dehydrogenase, mannitol-1-phosphatase, and fructose-6-phosphatase. Mannitol dehydrogenase, fructose-6-phosphatase, mannitol-1-phosphatase, and hexokinase activities were found in extracts of fruiting bodies. However, mannitol-1-phosphate dehydrogenase activity was not detected. Mycelial cultures were grown in an enriched liquid medium, and enzymes of the mannitol cycle were assayed in cell extracts of rapidly growing cells. Mannitol-1-phosphate dehydrogenase activity was also not found in mycelial extracts. Hence, evidence for a complete mannitol cycle both in vegetative mycelia and during mushroom development was lacking. The pathway of mannitol synthesis in L. edodes appears to utilize fructose as an intermediate.